2012
DOI: 10.2175/106143012x13347678384404
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption of Lead(II) in Aqueous Solution by Spent Mushroom Tricholoma lobayense

Abstract: The biosorption of lead(II) ions in both simulated and real wastewater by spent mushroom Tricholoma lobayense, was studied in this work. The results show a biomass with a high potential for removing lead ions from wastewater. The optimum pH for the adsorption is 4, and the adsorption process is fast. The best sorbent mass of the biomaterial is 5 g/L with an initial lead(II) concentration of 1 mmol/L. The process follows the Langmuir isotherm model, and the biosorption capacity of lead ions reaches to 210 mg/g,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…ACCEPTED MANUSCRIPT 14 the gel formation and divalent heavy metal cation binding properties of alginate can be found in literature [38][39][40][41]. As shown in this study, the dried beads had higher removal efficiency for lead and copper than the gel-type ones.…”
Section: Accepted Manuscriptsupporting
confidence: 63%
See 1 more Smart Citation
“…ACCEPTED MANUSCRIPT 14 the gel formation and divalent heavy metal cation binding properties of alginate can be found in literature [38][39][40][41]. As shown in this study, the dried beads had higher removal efficiency for lead and copper than the gel-type ones.…”
Section: Accepted Manuscriptsupporting
confidence: 63%
“…For these reasons, numerous researchers have been previously conducted for the treatment of lead and copper, such as chemical precipitation [11,12], ion-exchange [13,14], membrane filtration [15,16], flotation [17], and adsorption [18,19]. However, chemical precipitation is only optimal for high heavy metal ion concentration in wastewater and ion-exchange may cause secondary contamination when resins are regenerated by chemical reagents.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few reports are available on actual wastewater biosorption cases by species discussed in this review. For example Dai et al [87] …”
Section: Biosorption Capacities Of Side Stream Biomassesmentioning
confidence: 99%
“…The latter include: polycyclic aromatic hydrocarbons -PAHs- [34], fungicides [35,36], pesticides [37], petroleum [38], acid mine drainage [39,40] and textile effluents [41]. Several authors have tested different methods of SMS use for the bioremediation of Lentinus edodes to remove cadmium, chromium [42,43] and lead by Tricholoma lobayense [44]. More recently, Xu et al [45] reported the use of spent Agaricus bisporus to remove lead and cadmium from aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%